Optimum plant density of Digitaria eriantha for herbage accumulation and hydrological performance in a summer dominant rainfall zone. (18th February 2019) - Boschma, Suzanne P.; Murphy, Sean R.; Harden, Steven
Abstract: In the frost‐prone, summer dominant rainfall zone of northern NSW and southern Queensland, sown tropical grass pastures commonly establish with plant densities >26 plants per m 2, yet the optimum density for maximum herbage accumulation and hydrological performance is not known. A replicated, field study was established in northern NSW in November 2011, using five densities of Digitaria eriantha (digit grass): 0, 1, 4, 9 and 16 plants per m 2 and a range of agronomic and hydrologic measures was assessed. The results showed that the largest differences between plant densities in herbage accumulation, root depth, soil water extraction and rainfall refill efficiency occurred during the first 2 years; after this time, digit grass pastures with densities of ≥4 plants per m 2 responded similarly. Plant frequency increased with increasing plant density but the treatments did not converge. During the first two growing seasons, there was no effect of plant density on water use efficiency; however, by the third growing season, pastures with 4 plants per m 2 were the most water efficient. Overall, the results indicated that 1 plant per m 2 was too low to efficiently use resources, 16 plants per m 2 utilized the resources quickly then tended to stall, while 4–9 plants per m 2 was a good compromise between agronomic and hydrological response, achieving both herbage accumulation and sustainability goals. A practical management advantage of pastures with 4–9 plants per m 2 is they allow soil water resources to be available for a longer period of time and potentially provide the opportunity to establish legumes in the ensuing 24‐month period.